3‐1: Invited Paper: Super Bright 8K LCD with 10, 000 nit Realized by Excellent Light‐Resistance Characteristics of IGZO TFT Backplane. Issue 1 (25th September 2020) - Nishimura, Jun; Hara, Kengo; Daitoh, Tohru; Ohtsuki, Kenji; Takase, Kenji; Kawahira, Yuichi; Sakai, Akira; Minoura, Kiyoshi
Abstract : A 31.5″ 8K LCD with 10, 000 nit peak luminance, based on the Perceptual Quantization format in the ITU‐R Recommendation BT2100, has been developed with local dimming driving to perceive a high dynamic range in bright ambient environments. Good and uniform image quality has been confirmed due to excellent light‐resistance characteristics of IGZO TFT.